Comparative analysis of immunocompetence between females and males in the sea cucumber Apostichopus japonicus. Issue 63 (April 2017) - Jiang, Jingwei; Zhou, Zunchun; Dong, Ying; Gao, Shan; Sun, Hongjuan; Chen, Zhong; Yang, Aifu; Su, Hesheng
Abstract: In order to preliminarily understand the immune difference between females and males in the sea cucumber Apostichopus japonicus, the activities assay of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), phenoloxidase (PO), acid phosphatase (ACP) and alkaline phosphatase (ALP) with biochemical methods, the detection of PO isozymes with native-PAGE and catechol staining, and the test of antibacterial activities with bacterial growth curve determination method were performed in this study using cell-free coelomic fluid (CCF) and coelomocyte lysate supernatant (CLS) from females and males as the samples. The PO activities were not detected in the CLS and showed no significant difference between the CCF from females and males. However, totally five PO isozyme bands were detected in the CLS of females while only four were detected in the CLS of males after zymogram analysis. These results implied that the PO isozymes in the coelomocytes of viripotent A. japonicus were inactive under natural condition and may be activated by some certain treatments during native-PAGE, and PO might play different immune and physiological roles between females and males. In addition, the activities of SOD, CAT, POD and ALP in the CCF and the activities of CAT, POD, ACP and ALP in the CLS from males were all significantly higher than those from females. The results collectively suggested that in viripotent A. japonicus, the gender had a remarkable effect on the immunity, and the immunocompetence of males might have an advantage over that of females. Furthermore, the activities of all determined enzymes except PO and the number of detected PO isozymes showed higher values in CLS than in CCF, implying that in viripotent A. japonicus, the coelomocytes might take more immune responsibility in comparison with CCF. Highlights: The gender has remarkable effect on A. japonicus immunity. The reproductive development has important effect on A. japonicus immunity. The immunity of male A. japonicus might have an advantage over that of females. The effects of gender on immunity are species-specific in invertebrates.